“Vygotsky’s Inner Speech” Ajuda na solução de problemas matemáticos em TICs? "Vygotsky’s Inner Speech" Does it help in the solution of mathematical problems with the use of ICTs? - Guilherme, Alexandre; Brenner, Cristian Bobsin (Educação Matemática Pesquisa Revista do Programa de Estudos Pós-Graduados em Educação Matemática, 2017)
Resumo Após extensa e inconclusiva pesquisa bibliográfica por replicações de um estudo de Berk (1994) que relatou positivamente a relação entre o uso do Inner Speech, tão argumentado por Vygotsky, e o sucesso na resolução de problemas em crianças viu-se a oportunidade de elaborar um novo estudo, desta vez utilizando uma amostragem diferente de participantes composta em sua totalidade por alunos do curso de Matemática da PUCRS. Assim, fazendo uso de uma TIC, propomos investigar se há correlação entre o uso do Inner Speech e o sucesso na resolução de problemas matemáticos mesmo após a infância. A análise estatística usando SPSS resultou no valor-p 0,0357 e assim a hipótese nula (“Vygotsky’s Inner Speech não ajuda na solução de problemas matemáticos em TICs?) pode ser rejeitada. Abstract After extensive and inconclusive bibliographical research by replications of a study by Berk (1994) that reported positively the relationship between the use of the Inner Speech, so argued by Vygotsky, and children’s success in solving problems, we realized that there was an opportunity to elaborate a new study. However, this time using a different sample of participants that is composed in its entirety by students of the Faculty of Mathematics at PUCRS. Thus, making use of an ICT, we proposed to investigate if there is a correlation between the use of Inner Speech and the success in solving mathematical problems even after childhood. Statistical analysis using SPSS resulted in a p-value 0.0357 and therefore the null hypothesis ("Vygotsky’s Inner Speech does not help solve mathematical problems in ICTs?") can be rejected.